The influence of social media on Greek mothers’ attitudes and knowledge on breastfeeding - Mila, Katerina; Tympa, Eleni; Karavida, Vasiliki (International Journal of Public Health Science (IJPHS), 2025)
Recently, maternal breastfeeding in Greece has shown a positive trend. However, breastfeeding rates in Greece still lag behind those of other European countries. The participants of this quantitative study were recruited via social media and by personal connections. Data were gathered through questionnaire and analyzed utilizing descriptive statistics with SPSS 20. The study investigates: i) Trust levels among Greek mothers in social groups and their awareness of breastfeeding issues. ii) The impact of active participation in Greek parenting and breastfeeding support groups on Facebook on choosing and sustaining exclusive breastfeeding. iii) Whether engagement in social media groups positively influences the duration of exclusive breastfeeding and extends the overall breastfeeding period for infants. Out of the 776 participants, 727 were part of social media parenting groups. About 27.9% credited these groups for influencing their decision to breastfeed. Moreover, they perceived significant assistance from social media in staying well-informed about breastfeeding. The data collected confirms social media parenting groups positively influence breastfeeding mothers, enhancing knowledge, self-confidence, and deterring negative attitudes. This factor increases the likelihood of sustaining exclusive breastfeeding up to the recommended six months.